New experimental measurements of the H2-CO2 Collision-Induced Absorption in the [3907, 4770] cm−1 spectral range from 241 to 498 K - F. Vitali; S. Stefani; G. Piccioni; H. Tran; M. Snels; D. Grassi; C. Boulet; D. Biondi; A. Boccaccini (Icarus, 2026)

A simulator of the MAJIS instrument onboard the JUICE mission: Description and application to operational and scientific cases - C. Royer; P. Haffoud; Y. Langevin; F. Poulet; D. Bockelée-Morvan; E. D’Aversa; M. Cisneros-González; D. Grassi; N. Ligier; G. Piccioni; J. Carter; F. Tosi; et al. (Planetary and Space Science, 2025)

Attenuation of Cellular Senescence and Improvement of Osteogenic Differentiation Capacity of Human Liver Stem Cells Using Specific Senomorphic and Senolytic Agents - Allancer D. C. Nunes; Louise E. Pitcher; Henry A. Exner; Diego J. Grassi; Brittan Burns; Maria Beatriz Herrera Sanchez; Ciro Tetta; Giovanni Camussi; Paul D. Robbins (Stem Cell Reviews and Reports, 2025)
Expansion of adult stem cells in culture increases the percent of senescent cells, reduces their differentiation capacity and limits their clinical use. Here, we investigated whether treatment with certain senotherapeutic drugs would reduce the accumulation of senescent cells during expansion of human liver stem cells (HLSCs) while maintaining their differentiation capacity. Our results demonstrate that chronic treatment with the senomorphic XJB-5-131 or the senolytics cocktail D + Q reduced the number of senescent cells and significantly reduced the expression of senescence-associated genes and several inflammatory SASP factors in later passage HLSCs. Additionally, treatment with XJB-5-131 and D + Q improved the capacity of HLSCs to undergo osteogenic differentiation following extensive in vitro expansion. Overall, our data demonstrate that treatment with XJB-5-13 or D + Q results in a reduction in the percentage of replication-induced senescent HLSCs and likely other types of adult stem cells and improve the potential therapeutic use of later passage human stem cells. Graphical abstract

A novel pathogenic mutation in the ATP5MC3 gene of ATP synthase causing dystonia is associated with autophagic and lysosomal alteration - Clarissa Gissi; Elisa Zamprogno; Marina Comelli; Francesca D’Este; Federico Caicci; Bruno Grassi; Michela Carraro; Paolo Bernardi; Michael Zech; Giovanna Lippe; Camilla Bean (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Association of CHRNA5 Gene Variants with Crack Cocaine Addiction - Angelita P. Aroche; Diego L. Rovaris; Eugenio H. Grevet; Anderson R. Stolf; Breno Sanvicente-Vieira; Felix H. P. Kessler; Lisia von Diemen; Rodrigo Grassi-Oliveira; Claiton H. D. Bau; Jaqueline B. Schuch (NeuroMolecular Medicine, 2020)

Effects of 3-month high-intensity interval training vs. moderate endurance training and 4-month follow-up on fat metabolism, cardiorespiratory function and mitochondrial respiration in obese adults - Filippo Vaccari; Angelina Passaro; Andrea D’Amuri; Juana Maria Sanz; Francesca Di Vece; Eleonora Capatti; Benedetta Magnesa; Marina Comelli; Irene Mavelli; Bruno Grassi; Federica Fiori; Giulia Bravo; et al. (European Journal of Applied Physiology, 2020)

A quick combined approach for the characterization of a cliff during a post-rockfall emergency - G. Pappalardo; S. Mineo; S. Imposa; S. Grassi; A. Leotta; F. La Rosa; D. Salerno (Landslides, 2020)

Effect of alcohol use disorder on cellular aging - Luana Martins de Carvalho; Corinde E. Wiers; Peter Manza; Hui Sun; Melanie Schwandt; Gene-Jack Wang; Rodrigo Grassi-Oliveira; Ana Lúcia Brunialti Godard; Nora D. Volkow (Psychopharmacology, 2019)

Altered Nup153 Expression Impairs the Function of Cultured Hippocampal Neural Stem Cells Isolated from a Mouse Model of Alzheimer’s Disease - Lucia Leone; Claudia Colussi; Katia Gironi; Valentina Longo; Salvatore Fusco; Domenica Donatella Li Puma; Marcello D’Ascenzo; Claudio Grassi (Molecular Neurobiology, 2019)

Role of Mycobacterium avium lysate INF-γ, IL-17, and IL-2 ELISPOT assays in diagnosing nontuberculous mycobacteria lymphadenitis in children - Chiara Della Bella; Elisabetta Venturini; Savannah Devente; Paola Piccini; Simona Tapinassi; Leila Bianchi; Alessia Grassi; Marisa Benagiano; Heba F. Mustafa Alnwaisri; Carlotta Montagnani; Elena Chiappini; Wilbert Bitter; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Biliverdin Reductase-A Mediates the Beneficial Effects of Intranasal Insulin in Alzheimer Disease - Eugenio Barone; Antonella Tramutola; Francesca Triani; Silvio Calcagnini; Fabio Di Domenico; Cristian Ripoli; Silvana Gaetani; Claudio Grassi; D Allan Butterfield; Tommaso Cassano; Marzia Perluigi (Molecular Neurobiology, 2019)

Association Between the Serum Uric Acid Levels and Lacunar Infarcts in the Elderly - F. Crosta; U. Occhiuzzi; G. Passalacqua; E. Occhiuzzi; A. Cimini; D. Grassi; C. Ferri; C. Marini; C. Borghi; G. Desideri (Journal of Molecular Neuroscience, 2018)

The adipose tissue and the involvement of the renin–angiotensin–aldosterone system in cardiometabolic syndrome - F. Borghi; B. Sevá-Pessôa; D. M. Grassi-Kassisse (Cell and Tissue Research, 2016)

Gokyo Khumbu/Ama Dablam Trek 2012: effects of physical training and high-altitude exposure on oxidative metabolism, muscle composition, and metabolic cost of walking in women - E. Tam; P. Bruseghini; E. Calabria; L. Dal Sacco; C. Doria; B. Grassi; T. Pietrangelo; S. Pogliaghi; C. Reggiani; D. Salvadego; F. Schena; L. Toniolo; et al. (European Journal of Applied Physiology, 2016)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.

Copper recovery from aqueous solution by a modified industrial polymer - Miriam A. Martins Alho; Diego Grassi; Alicia Fernández Cirelli; Norma B. D’Accorso (Environmental Chemistry Letters, 2009)

An incentive mechanism for reducing emissions from conversion of intact and non-intact forests - Danilo Mollicone; Frédéric Achard; Sandro Federici; Hugh D. Eva; Giacomo Grassi; Alan Belward; Frank Raes; Günther Seufert; Hans-Jürgen Stibig; Giorgio Matteucci; Ernst-Detlef Schulze (Climatic Change, 2007)

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)

Ca 2+ channel inhibition induced by nitric oxide in rat insulinoma RINm5F cells - C. Grassi; Marcello D'Ascenzo; Alessio Valente; Gian Battista Azzena (Pflügers Archiv - European Journal of Physiology, 1999)

Gepirone and 1-(2-pyrimidinyl)-piperazine in vitro: human cytochromes mediating transformation and cytochrome inhibitory effects - L. L. von Moltke; D. J. Greenblatt; J. M. Grassi; B. W. Granda; S. M. Fogelman; J. S. Harmatz; S. J. Kramer; L. F. Fabre; R. I. Shader (Psychopharmacology, 1998)

Hemispheric asymmetries and bimanual asynchrony in left- and right-handers - Paolo Viviani; D. Perani; Franco Grassi; Valentino Bettinardi; Ferruccio Fazio (Experimental Brain Research, 1998)